From Collective Identity to Counter-Hegemony - Belolon, Handrianus Koli (PCD Journal, 2023)
In mass media, such as films, the Papuan region and people are still regarded as “the other", for example, portrayed as a people and region that needs to be civilized through various approaches. In addition, Papua is rich in natural wealth and culture, but instead of bringing prosperity, it become a source of new conflicts that threaten the existence and survival of the environment and the Papuan. This condition encourages young Papuan filmmakers and members of the Papuan Voices (PV) community to create an alternative narrative about Papua. Through documentaries produced collectively, they aim to present another side of Papua from the perspective of the Papuans. Using a poststructuralism approach elaborated with Gramsci's theory of hegemony, this study aims to explore the dynamics of collective identity formation and efforts to create counter-narratives as part of a counter-hegemony movement, namely by criticizing inequality and instilling solidarity for Papua. The analysis shows that the formation of PV’s collective identity is based on the history of Papuan suffering memories (memoria passionis) related to the experiences of injustice.